Effect of Motivation and Organizational Culture on Employee Performance in the Regional Government of Boalemo Regency - M. Yusuf Alfian Rendra Anggoro KR (International Journal of Scientific Multidisciplinary Research, 2023)
This research aims to analyze effect of motivation and organizational culture on employee performance in the Regional Government of Boalemo Regency. This research uses explanatory research. Population in the study are all employees of the Regional Government of Boalemo Regency consisting of the Secretariat, Agency, Department, District, and General Hospital with a total population of 1,569. Sample is 236 permanent employees using proportional random sampling techniques. Hypothesis testing in this research uses multiple linear regression tests via partial test.The research results show that motivation has a positive and significant effect on employee performance in the Regional Government of Boalemo Regency. Organizational culture has a positive and insignificant effect on employee performance in the Regional Government of Boalemo Regency